Optimasi Produksi dan Analisis Sensitivitas Produk “Bawang Goreng Crispy Yuk Riris” dengan Menggunakan Linear Programming - Roudlotul Badi'ah; Ahmad Syauqi; Rizna Ramadhani Winanda; Rusfian Effendi (Politeknik Negeri Batam, 2022)
This study aims to optimize production using linear programming with graphical and simplex methods accompanied by sensitivity analysis to determine the optimal product combination with maximum profit for the